2013
DOI: 10.1177/0143831x13484606
|View full text |Cite
|
Sign up to set email alerts
|

Declining autonomy at work in the EU and its effect on civic behavior

Abstract: The aim of this article is to show that social benefits may accrue from work environments that support autonomous forms of work. Based on social psychology, economics and philosophy approaches, the authors argue that autonomy is a basic human need which, when satisfied, enhances civic behavior. Using individual data from the EWCS, the article finds evidence of the positive effect of work autonomy on volunteer work and political/trade union activities. Overall, work autonomy has decreased over the last 15 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 37 publications
(38 reference statements)
3
28
0
2
Order By: Relevance
“…Results confirm the "Scandinavian exception": work autonomy levels in Denmark, Finland, the Netherlands and Sweden are above the EU average for all groups of workers and there is much less difference between clerical and manual workers and between low-skill and high-skill workers than in all other countries, where manual workers systematically suffer from below average work autonomy (Lopes et al., 2013). In addition, whereas work autonomy decreased in all other countries from 1995 to 2010, it stabilized or increased in Denmark, Finland, the Netherlands and Sweden.…”
Section: The Evolution Of Work Autonomy and Work Intensity In The Eusupporting
confidence: 58%
See 1 more Smart Citation
“…Results confirm the "Scandinavian exception": work autonomy levels in Denmark, Finland, the Netherlands and Sweden are above the EU average for all groups of workers and there is much less difference between clerical and manual workers and between low-skill and high-skill workers than in all other countries, where manual workers systematically suffer from below average work autonomy (Lopes et al., 2013). In addition, whereas work autonomy decreased in all other countries from 1995 to 2010, it stabilized or increased in Denmark, Finland, the Netherlands and Sweden.…”
Section: The Evolution Of Work Autonomy and Work Intensity In The Eusupporting
confidence: 58%
“…Our PCA also systematically revealed that work autonomy is a bidimensional phenomenon [7]. We nonetheless prefer not to keep Lopes et al (2013)'s terms and label instead the first factor "procedural autonomy" (PA) and the second factor "content autonomy" (CA).…”
Section: The Evolution Of Work Autonomy and Work Intensity In The Eumentioning
confidence: 99%
“…For Pateman (1970), direct participation at work is an essential element of democracy to the extent that it contributes to developing the qualities needed for responsible public action -self -confidence, public--spiritedness, willingness to cooperate, which results in enhanced political participation. That is, the more control and influence individuals exercise over their work life, the better equipped and more inclined they are to participate in community life (Lopes et al, 2014;Karasek and Theorell, 1990). For Pateman, in the absence of the vital training ground of low level participation, only few workers (certainly the most educated) would take up the opportunity offered in participative governance.…”
Section: Outlining a Solution To Re -Politicise Work And The Firmmentioning
confidence: 99%
“…Autonomy is an essential concept that plays a central role in many organizational theories such as motivation, job design (Hackman & Oldham, 1976), job demand-control (Karasek, 1979), and work stress (Spector, Dwyer, & Jex, 1988;Spector & Fox, 2003). Autonomy enables individuals to better grasp their roles in their job, it integrates them into their work (Morgeson, Delaney-Klinger, & Hemingway, 2005), motivates employees and stimulates learning (Morgeson, Campion, Garza, & Campion, 2003), increases wellbeing, self-esteem and creativity thereby increasing worker performance, and quality of relationships at work (Lopes, Lagoa, & Calapez, 2013).…”
Section: Employabilitymentioning
confidence: 99%
“…Lopes et al, (2013) argue that despite the increases in skilled level of workers in the EU, the level of autonomy declined between 1995 and 2010. An important exception of the overall decline would be that workers in Denmark, Finland, the Netherlands, and Sweden experienced an increase in autonomy in the last decades.…”
Section: Autonomymentioning
confidence: 99%